EFFECTIVENESS OF PEER GROUP SUPPORT IN THE APPLICATION OF ACUPRESSURE ON MENSTRUAL PAIN - Mahundingan, Rosari Oktaviana; Andriani, Dewi; Ramadhani, Dwi Yuniar (Journal of Vocational Nursing, 2025)
Introduction: One of various techniques in reducing menstrual pain is using relaxation techniques, namely acupressure. Group methods and peer group support are used to help teenagers overcome pain. The purpose of this study was to review Peer Group Support in the application of acupressure to menstrual pain in adolescent girls using the Self Determination model approach. Methods: This study used a quasi-experimental design with a pre-test and post-test design, of one group without a control group. The sampling technique used was simple random sampling.  The inclusion criteria were respondents who had menstruated, experienced menstrual pain, age at menarche between ≤12 years to ≥14 years, and menstrual duration <3 days to >7 days, as well as being cooperative and willing to be a respondent. The sample size was 35 adolescent girls. Results: The study with the Paired t-test showed that the Acupressure group experienced changes with a p-value = 0.03. The average increase in managing menstrual pain in t-count was 2.45. Conclusions: The pain level was measured at the beginning of menstruation, followed by the acupressure technique independently, then the pain level was measured again and showed a significant increase after the intervention in the group that did not experience acupressure. There were 2 respondents (5.7%) of pain, 26 respondents (74.3%) were at the mild pain level and 7 respondents (20%) were at the moderate pain level.